Effect of Perioperative Lidocaine, Propofol and Steroids on Pulmonary Metastasis in a Murine Model of Breast Cancer Surgery - Freeman, James (Cancers (Basel), 2019)
Addressing the hypothesis that anaesthetic-analgesic technique during cancer surgery might influence recurrence or metastatic spread is a research priority. Propofol, which has anti-inflammatory properties in vitro, is clinically associated with reduced risk of cancer recurrence compared with sevoflurane anaesthesia in retrospective studies. Amide local anaesthetics, such as lidocaine, have cancer inhibiting effects in vitro. Steroids have anti-inflammatory and immunosuppressive effects and are associated with improved recovery after major non-cancer surgery. We compared the effects of propofol, lidocaine and methylprednisolone on postoperative metastasis in a murine model of breast cancer surgery under sevoflurane anaesthesia. 4T1 tumour cells were introduced into the mammary fat-pad of female BALB/c mice and the resulting tumour resected seven days later under general anaesthesia with sevoflurane. Mice (n = 72) were randomized to four treatment groups: Sevoflurane alone (control); Propofol group received 5 mg.kg(−1); Lidocaine group received 1.5 mg.kg(−1) followed by 2 mg.kg(−1).h(−1) infusion; Methylprednisolone group received 30 mg.kg(−1) methylprednisolone. The primary outcome measure was pulmonary metastasis colony count, as assessed by in-vitro proliferation, two weeks post-operatively. This was achieved by treating the post-mortem lung tissue with collagenase IV, straining and culturing for 14 days prior to colony count. Compared with control, lidocaine and propofol each individually reduced pulmonary metastasis colonies; mean (SD) 846 (±581) vs. 88 (±52) vs. 34 (±44) respectively, (p = 0.0001 and p = 0.0001). Methylprednisolone increased lung metastasis, 2555 (±609) vs. 846 (±581), p = 0.0001. Post-operative hepatic metastatic disease and serum interleukin-6 and vascular endothelial growth factor levels were similar in all groups. In conclusion, in a murine model of breast cancer surgery during sevoflurane anaesthesia, propofol and lidocaine each decreased pulmonary metastasis, while methylprednisolone increased it.